EVALUATION OF DIAGNOSTIC PERFORMANCE OF USG GUIDED FNAC OF THYROID SWELLINGS: A PROSPECTIVE STUDY - Kumari Jyoti Mani; Neha Kumari; Arushi Kumar; Satyendra Sharma; Nageswar Sahu (Student's Journal of Health Research, 2023)
Background: USG-guided FNAC is a good preoperative screening technique when compared to FNAC and USG done separately for the diagnosis of a thyroid lesion. However, there is little evidence in the literature that emphasizes the importance of USG-guided FNAC as the first step in the investigation of thyroid lesions. Aim: Our study aims to see the sensitivity and specificity, adequacy, and diagnostic accuracy of USG-guided FNAC taking histopathology as a gold standard. Methods: This Hospital-based prospective observational study was carried out on patients who attended the OPD and/or IPD and underwent surgery in the Department of Otorhinolaryngology. Results: The sensitivity, specificity, and diagnostic accuracy of ultrasound-guided FNAC for thyroid lesions were 58.82%, 98.18%, and 88.89% respectively taking Bethesda categories 1 to 3 as benign and categories 4 to 6 as malignant. The positive likelihood ratio and negative likelihood ratio are 32.32 and 0.42 respectively. Positive predictive value and negative predictive value were 90.91% and 88.52%. The diagnostic accuracy of USG-guided FNAC for thyroid lesions in the present study is 88.89% and adequacy is 93.05%. Conclusion: Further study of a larger number of cases is desirable. US-FNAC is an expensive procedure as compared to palpable FNAC. Recommendation: We recommend the application of USG guide FNAC as the first step in the investigation of thyroid lesions along with a detailed interdepartmental correlation to make the diagnosis before surgery.